2023
DOI: 10.3390/mi14081590
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Machining Parameters to Minimize Cutting Forces and Surface Roughness in Micro-Milling of Mg13Sn Alloy

Ali Ercetin,
Kubilay Aslantaş,
Özgür Özgün
et al.

Abstract: This comprehensive study investigates the micro-milling of a Mg13Sn alloy, a material of considerable interest in various high-precision applications, such as biomedical implants. The main objective of the study was to explore the optimizations of variable feed per tooth (fz), cutting speed (Vc), and depth of cut (ap) parameters on the key outcomes of the micro-milling process. A unique experimental setup was employed, employing a spindle capable of achieving up to 60,000 revolutions per minute. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…From Table 5 can be seen that vc, vf, and doc, are lower probabilities compared to other parameters, where they have a significant effect on the response Ra. Similar results of Ra can be found in [31] and [30]. By VIF equal to 1 at all parameters indicated that they have no correlations among the predictors in the model.…”
Section: Resultssupporting
confidence: 79%
“…From Table 5 can be seen that vc, vf, and doc, are lower probabilities compared to other parameters, where they have a significant effect on the response Ra. Similar results of Ra can be found in [31] and [30]. By VIF equal to 1 at all parameters indicated that they have no correlations among the predictors in the model.…”
Section: Resultssupporting
confidence: 79%
“…However, it differed from the previous one in that it took into account the influence of tool edge radius on tool clearance face wear in the micro-end milling process. The study by Ercetin and colleagues is devoted to the consideration of machining parameter optimization issues for minimizing cutting forces and surface roughness in the micro-milling of Mg13Sn alloy [77]. Cai L. and colleagues proposed an analytical model for calculating the temperature during milling with minimum quantity lubrication (MQL) of AISI D2 steel [78].…”
Section: Cutting Force Calculation Using Analytical Modelsmentioning
confidence: 99%
“…The main influencing factors must include the dynamic motions of the spindle-holder-tool assembly. During cutting, the spindle speed of the micro-machine is usually higher than 10,000 revolutions per minute to ensure a high cutting efficiency in micro-milling [3]. Therefore, the centrifugal force induced by rotational speeds and the gyroscopic effect induced by high speeds are inevitably accompanied by high spindle speeds.…”
Section: Introductionmentioning
confidence: 99%